A new species of the genus Monopelopia from South Brazil, with keys to the Neotropical–Nearctic species (Diptera: Chironomidae: Tanypodinae) - de Oliveira, Caroline Silva Neubern; Mendes, Humberto Fonseca; Da Silva, Mário Antônio Navarro (Zootaxa, 2010)
A new species, Monopelopia paranaense is described and illustrated, based on immatures collected in a little pond in Parana State (South Brazil) and adults reared in laboratory. Keys to males, larvae and pupae of all species of the genus Monopelopia Fittkau known in the New World are also provided.